1980
DOI: 10.1007/bf01907693
|View full text |Cite
|
Sign up to set email alerts
|

Vagal and sympathetic reflexes of left ventricular origin on the efferent activity of cardiac and renal nerves on anaesthetized cats

Abstract: The influence of reflexes of left ventricular origin on the postganglionic sympathetic activity and heart rate was investigated in anaesthetized cats. The experiments were to clarify 1. whether there are regionally different reflex adjustments due to an activation of ventricular receptors, 2. whether an increase of left ventricular diastolic pressure, which is known to activate afferent vagal fibres, causes an inhibition of sympathetic activity, 3. whether a coronary artery occlusion can activate a pressor ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The intact groups in their study showed only hypotensive response. Equally impressive data by Vogt and Thamer (22) in the SAD cat demonstrated that significant reductions in RNA and inferior cardiac nerve activity were evoked with LAD occlusion associated with a prominent hypotension. In this latter study, the systemic responses, except for the reduction in ABP, were abolished with vagotomy.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The intact groups in their study showed only hypotensive response. Equally impressive data by Vogt and Thamer (22) in the SAD cat demonstrated that significant reductions in RNA and inferior cardiac nerve activity were evoked with LAD occlusion associated with a prominent hypotension. In this latter study, the systemic responses, except for the reduction in ABP, were abolished with vagotomy.…”
Section: Discussionmentioning
confidence: 94%
“…However, in some patients during myocardial infarction and in dogs during coronary occlusion, a depressor response and bradycardia have been observed (8,19,25). Since the inhibitory and excitatory responses have been observed in vagotomized dogs and cats in which mechanical changes were minimal (22), these contrasting affects were most likely due to reflexes mediated by sympathetic afferent nerves.…”
Section: ) Supported By National Institutes Of Health Grant # Hl-225mentioning
confidence: 88%